A rare differential of acute abdomen: a case of internal hernia presenting as small bowel obstruction - S., Shahid Afridi; Banerjee, Divya Jyoti (International Surgery Journal, 2024)
Internal hernias, though uncommon, are crucial to consider when diagnosing intestinal obstruction. They typically arise from developmental abnormalities, less frequently from acquired issues. Developmental causes include abnormal or incomplete development of the mesentery or gut rotation. Surgery is the most common cause of acquired internal hernias, particularly laparoscopic gastrojejunostomy or duodenojejunostomy repair procedures. Internal hernias usually present with intestinal obstruction symptoms. Imaging plays a vital role in diagnosis. While an upright abdominal X-ray may show signs of obstruction, CT scanning is the definitive investigation. This report describes an 18-year-old male who presented with generalized abdominal pain for eight days and no stool or gas passage for the past three days. After confirmation of a mesenteric hernia through ultrasound and CT imaging, emergency laparotomy surgery was performed. Due to gangrenous bowel, resection was not possible, so an ileostomy was created. The tissue sample was sent for histological examination. Surgery remains the definitive treatment for internal hernias.